Cuidado à família enlutada: intervenções realizadas em um hospital público do interior do Estado de São Paulo - Bérgamo, Daniela Carvalho (Universidade Federal de São Carlos, 2018)
Introduction: the experience of the mourning process is unique and it will develop according to the characteristics of the bereaved and the circumstances of death, which has been occurring more and more in hospitals due to the technological advances in health. Studies show the importance of caring for the bereaved who are experiencing difficulties in drawing up the loss in order to avoid the establishment of complicated mourning. From the implantation of the National Policy of Humanization, changes in health care models were proposed aiming the integral care and redefinition of the hospital's function in the health system, opening space to reformulate the performance according to the characteristics of the service and patient´s need, allowing for a rethinking of care practices including the social support network involved. Objective: this research aimed to understand the repercussions of the interventions performed by a public hospital in the interior of the state of São Paulo in the process of elaboration mourning families of patients who died in the institution and promoting a discussion about grief assistance and the accomplishment of these things by hospitals. Method: this is a qualitative research used was a comprehensive approach based on the sociological phenomenology described by Minayo (2014), the instrument used was the semi-structured interview with bereaved relatives who attended the Grief Reception Group and the analysis of the material was collected through the content analysis of Bardin (1977). Results: the bereaved relatives expressed suffering to face the bereavement even of a predictable death and the need for a bereavement to be heard and to be understood in the face of the feelings and difficulties experienced that goes beyond the loss. They identified as favorable the interventions performed by the hospital, for being reminded, not to feel alone and to the possibility to exchange these experiences with other pelople who are experiencing similar situation, to understand the natural reactions and finding comfort and support to face the mourning. Final considerations: the research shows many possibilities of mourning interventions that can be performed in several places. It also showed the benefit of bereavement care being performed in hospitals because of the the bond already established previously and the comfort felt by the family in contact with the health team after the patient´s death. The mourning of deaths understood as natural and expected, despite bringing suffering to families is neglected. There is then a need to rethink the health practices of institutions, including hospitals, to change the current reality of carelessness in mourning.
Care to the bereaved Family: actions carried out in a public hospital in the country of São Paulo
Keywords: Família enlutada; Hospital; Cuidado pós-morte; Bereaved family; Postmortem care; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA